Creative Economy in Urban Planning Policies: a Systematic Review - Silva, Luiz Felipe da; Miyasaka , Elza Luli; Forcel, Priscila Kauana Barelli; Olivatto, Tatiane Ferreira; Andrade, Júlia Neves (ANAP Brazil, 2025)
ABSTRACTObjective – This study aims to analyze how the creative economy is incorporated into and influences urban planning policies.Methodology – A qualitative approach is adopted, based on a systematic review of academic literature using publications indexed in the Scopus database.Originality/Relevance – The research is justified by the growing relevance of the topic on public and academic agendas, as well as the need to understand its territorial impacts.Results – The results indicate a predominance of approaches focused on the rehabilitation of degraded areas, the promotion of cultural tourism, and the stimulation of innovation as urban development strategies. Recurrent challenges, such as gentrification, the instrumentalization of culture, and inequality in accessing the benefits of creative policies, were also identified.Theoretical/Methodological Contributions – The study methodologically combines systematic review and bibliometrics to map the intellectual structure of the field, identifying the main theoretical approaches, trends, and gaps at the interface between the creative economy and urban planning.Social and Environmental Contributions – The research warns of the social risks of gentrification and exclusion, advocating for inclusive and participatory policies that link economic development with social cohesion and sustainability to create more just cities.
Keywords: Creative Economy; Urban Planning; Bibliometric Analysis